Important role and benefits of Azolla plants in the management of agroecosystem services, biodiversity, and sustainable rice production in Southeast Asia - Siriyaporn Chanapanchai; Wahdan Fitriya; Ida Bagus Made Artadana; Kanyaratt Supaibulwatana (Journal of Integrative Agriculture, 2025)
Global warming and climate change have made food production through conventional agriculture inefficient, and their effects on livestock and crop cultivation are leading to disruptions in the food supply. The troubles are severe in regions suffering from improper land management and unsustainable practices. The Bio-Circular-Green (BCG) economic model, designed to reduce and recycle resources by using environmentally friendly procedures, has been developed. The Azolla plant represents an interesting model for BCG and for enhancing community networks in Southeast Asia (SEA) because it provides multipurpose materials. Azolla can be used for various applications in agriculture such as biofertilizer and animal feed. However, our understanding and utilization of Azolla are limited. Moreover, collaboration among farmers is insufficient to maximize the benefits of Azolla. In this study, we provide a comprehensive review of the role of Azolla in agriculture. We review the main properties of Azolla as biofertilizers, especially regarding rice production and the interaction with cyanobacteria. For livestock, we discuss procedures to use Azolla in animal feed and evaluate the ingredients of the meal. In addition, we discuss product qualities from livestock treated with Azolla in the diet. This review also describes Azolla-based farming, which is designed for efficient land use and promotes nutrient cycling. Hence, we show that the Azolla plant is one of the key factors for farm-based agroecosystem services which can drive sustainable bioresource management in SEA. Moreover, we also propose the potential development of Azolla to improve its properties as a biofertilizer, a functional feed for animals and humans, and a feedstock for bio-oil production.